Beyond Anti-Conquest: Unearthing the Botanical Archive with Locative Media - Didur, Jill (Intermédialités / Intermediality, 2020)
This article introduces the Alpine Garden MisGuide / Le Jardin alpin autrement, a locative media project that endeavours to bring the complex cultural and historical insights of the paper archive on botanical exploration into dialogue with the embodied experience of visiting the living archive of contemporary botanic gardens. Recently created mobile guides to botanic gardens tend to fall back on the discourse of “anti-conquest”—where the colonial subject claims innocence even as s/he subordinates the other to their gaze—to frame their collections for the public. Taking a decolonial approach, this essay explores how the affordances of the MisGuide’s locative platform presents opportunities to challenge innocent or nostalgic presentations of botanic gardens’ collections and engage garden visitors in a more complex account of the influence of colonialism in the history of gardens and the environment.